Morphological, Secondary Metabolite and ITS (rDNA) Variability within Usnic Acid‐Containing Lichen Thalli of Xanthoparmelia Explored at the Local Scale of Rock Outcrop in W‐Alps. Issue 6 (27th May 2017) - Matteucci, Enrica; Occhipinti, Andrea; Piervittori, Rosanna; Maffei, Massimo E.; Favero‐Longo, Sergio E.
Abstract : Lichen secondary metabolites (LSMs) are regarded with interest for valuable biological properties, but chemical variability among/within lichen taxa has been only fragmentarily characterized by advanced analytical techniques. Knowledge of variability at a local geographic scale has been particularly neglected, while it should address the collection of chemically homogeneous materials to test and exploit LSMs. Here we evaluated the chemical variability of 48 Xanthoparmelia specimens from two rock outcrops in Western Italian Alps, representative of nine morphotypes and sixteen rDNA ITS haplotypes. Qualitative and quantitative analyses were performed by HPLC‐DAD‐ESI‐MS2 and UPLC‐HDR‐DAD, respectively, and revealed the occurrence of 18 LSMs. Chemical partition allowed distinguishing six chemical groups, only partially overlapping with distinct morphotypes and three divergent haplotype groups, which, overall, accounted for the co‐occurrence of different taxa only in part identifiable with species described for Europe. Some morphotypes were variable in presence and concentration of LSMs, and chemical divergences also characterized single ITS haplotypes. Accordingly, the collection of chemically homogeneous materials, even at a local scale, may be not properly addressed by morphological features and ITS barcoding, and should be confirmed by a specimen‐level chemical characterization. Abstract :